Bentuk Distribusi Jumlah Kasus Covid-19 Di Kabupaten Timor Tengah Utara - Marcelina Nikola De Albergati Luty; Eva Binsasi; Cecilia Novianti Salsinha (Program Studi Matematika, Universitas Timor, 2024)
Corona Virus Disease (Covid-19) is an infectious disease that attacks the respiratory system caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which was discovered at the end of December 2019 in Wuhan City, Hubei Province, China. In Indonesia, the first Covid-19 case was discovered on March 2 2020. The number of Covid-19 cases in Indonesia continued to increase over time, until it spread very quickly throughout the region, including North Central Timor Regency (TTU) based on data obtained from the District Health Office. TTU's number of Covid-19 cases continues to increase every day until December 2021. The aim of this research is to find out the form of distribution that corresponds to data on the number of Covid-19 cases in TTU Regency. This type of research is quantitative research. The data used is data on the number of Covid-19 cases for July 2020-December 2021 obtained from the TTU District Health Service Office. This research uses the distribution fitting method and parameter estimation using the Maximum Loglikelihood Estimation (MLE) method. The research results show that a suitable distribution for data on the number of Covid-19 cases is a Poisson distribution with the same average parameter λ = 9.073771.